Minidictionary of geography - Mayhew, Susan (Oxford University Press, 1994)
This pocket-sized dictionary is a comprehensive and up-to-date guide for all students studying GCSE Geography courses. Suitable for quick reference or revision, its 1,500 entries provide explanations of all the major terms in the National Curriculum. This mini-reference offers step-by-step explanations of basic skills, a data file with important statistics for 20 countries and helpful cross-references. The book is designed for schoolchildren studying geography up to GCSE level, and is useful also for A-level students. Susan Mayhew is the author of "The Concise Oxford Dictionary of Geography" and "Penguin Passnotes Geography".